Facile Construction of Self-Healing Polydopamine-Based Composite Coating Protection of Copper From NaCl Solution - Chen, Wei; Fan, Juanjuan; Jiang, Yueyue; Li, Shouting; Ying, Ye; Yang, Haifeng (Frontiers in Materials, 2022)
The self-healing composite coating is successfully constructed on the copper surface by embedding 8-hydroxyquinoline into polydopamine (denoted as PDA@8-HQ). The composition of coating is confirmed with XPS, FTIR and Raman methods. The inhibition efficiency and self-healing capability of PDA@8-HQ coating are evaluated by using electrochemical techniques and FE-SEM. As a result, PDA coating embedded with 0.02 M 8-HQ exhibits the best protection of copper from salt corrosion. In case of damage to such coating by external force, it demonstrates excellent self-healing capability through the reaction of the released 8-HQ and the exposure copper to generate the complex product.